Manajemen Mutu Pendidikan di SMP Negeri 30 Semarang - Muhammad Luthfi Hanif; Kasan Bisri (Program Studi Manajemen Pendidikan, 2026)
This study aims to explore the implementation of educational quality management at SMP Negeri 30 Semarang, the challenges encountered, and the solutions adopted to improve the quality of education. The background of this study highlights the importance of quality as a key factor in school competitiveness in the global era. The research was conducted during the School Field Practice (PLP) program using a qualitative approach. Data were collected through observations, interviews with teachers and the vice principal for academics, and documentation. The findings show that quality management at SMP Negeri 30 Semarang has been implemented through planning based on the school’s vision, mission, and objectives; the execution of academic and non-academic programs aligned with the National Education Standards (SNP), and continuous supervision through monitoring and evaluation. The main challenges include teachers’ heavy workload, limited funding, and suboptimal human resource competencies. Solutions are carried out through proportional task distribution, the use of digital technology, collaboration with school committees and external partners, and capacity building for teachers and staff through training.